Integration of Philosophy of Science, Educational Quality, and Educational Administration in a Modern Conceptual Perspective - Ine Rahayu Purnamaningsih; Ahmad Syahroni; Yayah Asiah Nurpadilah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study examines the conceptual and philosophical foundations that shape the relationship between the philosophy of science, educational quality, and modern educational administration. Through library research and conceptual analysis, the study demonstrates that educational quality is not a neutral technical construct, but rather a product of the epistemological assumptions and axiological commitments underlying educational systems. Traditions of rationalism, empiricism, constructivism, and critical realism yield distinct understandings of legitimate knowledge and methods of assessing learning, while value orientations determine the moral goals upon which educational quality is measured. Further analysis demonstrates that educational administration functions as an operational mechanism that translates epistemic and value principles into policies, governance, accountability, and institutional practices. A comparison of the philosophy of science paradigm and the shifting administrative paradigm confirms that managerial innovations such as evidence-based policies, continuous quality improvement, and school-based management are rooted in specific philosophical assumptions. This study then offers an integrative conceptual model that positions educational quality as the result of a dynamic interaction between epistemology, axiology, and administrative praxis. The research findings provide theoretical contributions by clarifying the philosophical foundations of quality assurance and offering a framework for developing reflective, value-based, and epistemically coherent educational governance.